Design of hierarchically porous carbon frameworks for enhanced CO2 capture performance. Issue 2 (April 2023) - Zhao, Xinfu; Nie, Yihao; Yi, Xibin; Yu, Shimo; Zhang, Jing; Liu, Xiaochan; Liu, Sijia; Yuan, Zhipeng
Abstract: To reduce the environmental impact of CO2, CO2 capture has become an area of research interest. Hierarchically porous materials have been certified as efficiency CO2 capture adsorbents. This work is aimed to construct hierarchically porous carbon frameworks (CPI-TPUs) with enhanced CO2 capture performance. CPI-TPUs are derived from polyimide (PI)/thermoplastic polyurethane (TPU) composite aerogels (PI-TPUs) with mesopores and macropores. Accordingly, the obtained CPI-TPU2 exhibits an improved CO2 uptake capacity (2.21 mmol/g, 298 K) compared to the pure CPI and PI-TPUs due to the synergistic effect of hierarchically pores, higher specific area and electron-rich heteroatoms. Specially, CPI-TPUs with pore volume ratio of mesopores/macropores to total pores in a range of 6–21 show high CO2 uptake performance. These CPI-TPUs with high CO2 adsorption capacities and suitable isosteric adsorption heats (Qst ) are promising CO2 adsorbents. Graphical Abstract: ga1 Highlights: A new method to fabricate hierarchically porous carbon frameworks is described. CPI-TPU2 exhibits an improved CO2 uptake capacity of 2.21 mmol/g (298 K, 1.0 bar). CPI-TPUs with a (Vmeso +Vmacro )/Vtot value of 6–21 show high CO2 uptake performance. CPI-TPU2 with a Qst value of 43.2 kJ mol -1 is a promising CO2 adsorbent.